2008
DOI: 10.1097/jto.0b013e318180270b
|View full text |Cite
|
Sign up to set email alerts
|

Locally Advanced Non-small Cell Lung Cancer: The Past, Present, and Future

Abstract: Approximately a third of patients with newly diagnosed non-small cell lung cancer (NSCLC) have locally or regionally advanced disease not amenable for surgical resection. Concurrent chemoradiation is the standard of therapy for patients with unresectable locally advanced NSCLC who have a good performance status and no significant weight loss. Prospective studies conducted over the past two decades have addressed several important questions regarding systemic therapy and thoracic radiation. They include the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 93 publications
(96 reference statements)
2
59
0
2
Order By: Relevance
“…This result also indicated that CEA as an unfavorable prognostic maker for NSCLC patients. 3 Hazard ratio (HR) for death with respect to normal CA125 concentration. 4 Bold-italic values are statistically significant (p < 0.05).…”
Section: Clinicopathological Characteristics Of Nsclc Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result also indicated that CEA as an unfavorable prognostic maker for NSCLC patients. 3 Hazard ratio (HR) for death with respect to normal CA125 concentration. 4 Bold-italic values are statistically significant (p < 0.05).…”
Section: Clinicopathological Characteristics Of Nsclc Patientsmentioning
confidence: 99%
“…Despite the improvements in the diagnosis and treatment in recent years, the 5-year survival rates of lung cancer remain as low as 16 %, with significant variation depending on the stage of disease at the time of diagnosis [2]. The majority of people diagnosed with NSCLC are at a late stage and therefore not suitable for surgery [3]. The prognosis of advanced NSCLC patients is variable and may depend on different prognostic factors, including biological features of cancer cells.…”
mentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for 80-85 % of lung cancer cases, and approximately 30 % of patients have unresectable, locally advanced disease at diagnosis [2]. Sause et al reported that combining chemotherapy and radiotherapy brought a further survival benefit [3].…”
Section: Introductionmentioning
confidence: 99%
“…Management of patients with locally advanced non-small cell lung cancer (NSCLC) has changed significantly in the past few years (1,2). Concomitant chemoradiotherapy is the standard of care in fit patients (Eastern Cooperative Oncology Group [ECOG] performance status grade, 0-1) (3).…”
mentioning
confidence: 99%